2011
DOI: 10.1530/rep-11-0060
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a conserved function of heart and neural crest derivatives expressed transcript 2 in mouse and human decidualization

Abstract: Previously we showed that Hand2 mRNA levels dramatically increase in mouse uterine endometrial stromal cells as they undergo decidualization in vivo. However, very little is still known about the expression and function of this transcription factor in the mouse or human uterusdecidualization. Therefore, the current study was undertaken to provide a more detailed assessment of Hand2gene expression and function in the mouse uterus during the periimplantation period and also in mouse plus human endometrial stroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 52 publications
3
66
0
Order By: Relevance
“…HAND2 is robustly expressed in mouse uterine stroma by day 3 of gestation but is notably absent in the epithelium. Its stromal expression persists through the peri-implantation phase and is detectable until day 8.5 of pregnancy (92). Recent mouse genome-wide PGR binding studies indicated that Hand2 is a direct target of regulation by this receptor (22).…”
Section: Steroid-induced Epithelial-stromal Crosstalk Originating In mentioning
confidence: 99%
“…HAND2 is robustly expressed in mouse uterine stroma by day 3 of gestation but is notably absent in the epithelium. Its stromal expression persists through the peri-implantation phase and is detectable until day 8.5 of pregnancy (92). Recent mouse genome-wide PGR binding studies indicated that Hand2 is a direct target of regulation by this receptor (22).…”
Section: Steroid-induced Epithelial-stromal Crosstalk Originating In mentioning
confidence: 99%
“…3C) and/or heart and neural crest derivatives expressed 2 (Hand2)? A recently described bHLH transcription factor required for decidualization [50,51], Hand2 has yet to be matched with an endometrial interacting partner. 4) Does abrogation of Tcf23 in the mouse uterus cause …”
Section: Role Of Tcf23 In Endometrial Decidualizationmentioning
confidence: 99%
“…PR directly induces HAND2 expression in human stromal cells (Mazur et al 2015 ). In mice, HAND2 is expressed in the endometrial stroma at day 3 of pregnancy, consistent with PR-dependent induction (Huyen and Bany 2011 ). Importantly, uterine ablation of Hand2 expression ( PR…”
Section: The Role Of Stromal Pr In Er Antagonismmentioning
confidence: 71%